pension risk disclosure in FTSE100 firms - wang, yilin (2013)
Pension risk reporting is attracting attention from investors, regulators and corporations. The IASB, ASB require principle actuarial assumptions, the funding status etc. to be disclosed in the annual reports. However, these regulations are not mandatory. The investors need more risk related information to adjust their investment strategy. Corporations, on the other hand, either want to signal their pension risk management skills or hide risks from the public. Under this circumstance, we find a varied level of risk disclosure among FTSE100 firms.